PENAFSIRAN HUKUM DALAM MENENTUKAN UNSUR-UNSUR KELALAIAN MALPRAKTEK MEDIK (MEDICAL MALPRACTICE - Widodo Tresno Novianto (Faculty of Law, Universitas Sebelas Maret, 2015)
AbstractStruggle interpretation of the law to determine the elements of errors/omissions in Medical Malpractice often encountered in the process of resolving a medical action performed by a doctor with allegations of errors/omissions/negligence and irregularities health care procedures/professional errors/omissions professionals. Legal battle to determine the elements of negligence in Medical Malpractice is situated on the difference between the interpretation and application of ordinary criminal offenses set out in the Criminal Code and the crime of medical. Where ordinary crime that primarily focuses on the factor of